Recherches Interdisciplinaires Sur Les Sites Funéraires Des Régions De La Bagoué Et Du Poro En Côte d’Ivoire - Kiénon-Kaboré Timpoko Hélène; Bouadi Kouadio René; Thia-Assouan Aline; Atta Kouamé; Kouassi Firmin; Coulibaly Drissa; Dappa Joëlle; Tui Lah Louis; Dougan Salia; Kazio Didjé Jacques (European Scientific Journal, ESJ, 2017)
Within the framework of the project: "contribution of the social sciences and the pharmacology to the process of the sustainable development and struggle against poverty in the region of Poro and Bagoué", a first campaign of archaeological and anthropological research has been undertaken in the localities of Tongon and Poungbè in the region of Bagoue, located in the north of Côte d’Ivoire, approximately 50 km in the north of Korhogo city; administrative center of the region of Poro. This mission, which enters into a multidisciplinary approach, deals with the funeral sites of Nawavogo and Daovogo that is presented by traditionnists as former metallurgists graves to whom we attribute the sites of restriction of the iron, extraction of the ore, and the habitat in the locality of Nawavogo and Poungbè. The first results based on the topographic analysis of sites, the preliminary study of the ceramic, and the two excavated graves show many specific funeral practices and a technical know-how of the populations which have occupied these spaces. The scientific, cultural and patrimonial value of these data has already explained all the interest to make the study of this region works deeper.